Three-Stage ISD Matrix (TIM) Tool to Review the Impact of Inherently Safer Design Implementation - Zainal Abidin, M. (Institution of Chemical Engineers, 2016)
Inherently safer and friendlier plant design offers a simpler, cheaper, safer solution that consumes less energy, requires less maintenance, and produces less waste and pollution. It is a solution that the chemical industry needs to continually adopt in the years ahead. Nevertheless, obtaining an inherently safer process/technology with respect to all potential hazards is quite unfeasible and may lead to conflicts in the alternative process selection. To resolve safety conflicts, thorough understandings of all the hazards associated with the process options are vital. This paper presents a systematic screening procedure for reviewing inherently safer design alternatives using a combination of three-stage ISD matrix tool and guide word approach. The proposed methodology was applied to the ammonia supply system with the objective to understand the trade-off of inherent safety toward the overall process. The results show that the proposed tool is capable of helping users understand the impact of modification toward the safety and implementation cost. Â© 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.